Galactic Astronomy - Binney, James (Princeton Series in Astrophysics Ser., 1998)
This is a treatment of the phenomenology of galaxies. The text draws on observations of both our own galaxy, the Milky Way, and of external galaxies. It emphasizes the observational basis for current understanding of galactic astromony in the late '90s.